Viral surface glycoproteins, gp120 and gp41, as potential drug targets against HIV-1: Brief overview one quarter of a century past the approval of zidovudine, the first anti-retroviral drug - Catia Teixeira (2011)
The first anti-HIV drug, zidovudine (AZT), was approved by the FDA a quarter of a century ago, in 1985. Currently, anti-HIV drug-combination therapies only target HIV-1 protease and reverse transcriptase. Unfortunately, most of these molecules present numerous shortcoming; such as viral resistances and adverse effects. In addition, these drugs are involved in later stages of infection. Thus, it is necessary to develop new drugs that are able to block the first steps of viral life cycle. Entry of HIV-1 is mediated by its two envelope glycoproteins: gp120 and gp41. Upon gp120 binding to cellular receptors, gp41 undergoes a series of conformational changes from a non-fusogenic to a fusogenic conformation. The fusogenic core of gp41 is a trimer-of-hairpins structure in which three C-terminal helices pack against a central trimeric-coiled coil formed by three N-terminal helices. The formation of this fusogenic structure brings the viral and cellular membranes close together, a necessary condition for membrane fusion to occur. As gp120 and gp41 are attractive targets, the development of entry inhibitors represents an important avenue of anti-HIV drug therapy. The present review will focus on some general considerations about HIV, the main characteristics of gp120, gp41 and their inhibitors, with special emphasis on the advances of computational approaches employed in the development of bioactive compounds against HIV-1 entry process.